(untitled) (Journal of Event, Tourism and Hospitality Studies, 2022)
Quick Response code or QR code is a type of bar code that is used widely in many organizations including in tourism to provide various information. This study aims to investigate tourists’ expectations of information provided by QR codes and to study tourists’ satisfaction with QR codes on Street Art in Songkhla old town, Thailand. Quantitative research design was employed in this study. 100 Thai and non-Thai respondents from each of the two phases of data collection answered each set of two questionnaires. Majority of the tourists responded for the need of QR codes to represent Street Art paintings in Songkhla old town as they would like to know the meaning of the paintings in more detail. The language used in QR codes should be English and Thai. The majority of the tourists showed satisfaction with QR code as information sources for Street Art paintings in terms of design, codes’ easy usage, and its accessibility which is not complicated. The results of this study can facilitate travelers’ rapid and easy access to tourism information. The QR codes can improve tourists’ experience by giving background information behind each painting related to history, culture and local ways of life. It helps both tourists and locals to discover more information about the cultural heritage they inherited and to enhance their awareness of heritage preservation. Tourism stakeholders and policy makers also benefit from this study as the information can be used to develop the QR codes for other tourist destinations. Additionally, street art plays an important role in creating creativity in the city and contributes in promoting Songkhla Old Town. It is considered as a tool to drive the local economy.